2019
DOI: 10.29271/jcpsp.2019.06.524
|View full text |Cite
|
Sign up to set email alerts
|

Is Adenotonsillar Size a Significant Factor on Voice in Children Undergoing Adenotonsillectomy?

Abstract: Methodology: A total of 57 patients, who have been diagnosed with chronic adenotonsillitis and operated for obstruction or infection, were included in the study. Patients were divided into two groups according to their palatine tonsil sizes. Each patient performed voice analysis preoperatively and one month postoperatively, recruiting both objective and subjective methods. F0, jitter % and shimmer % values were assessed with objective methods; while subjective methods evaluated pediatric voice handicap index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 10 publications
(11 reference statements)
0
19
0
Order By: Relevance
“…40,41 The softwares used in the included studies were the Computerized Speech Lab, 12,24,29 the Multi-Dimensional Voice Program, [13][14][15]22,24,41 the standardized commercial voice analysis system, 16 the Praat software, 23,26,28,41 and the XION Medical DIVAS 2.5 Digital Voice Analysis. 25 The aerodynamic assessment includes the transglottic flow and the subglottic pressure to understand the variations in pressure and airflow during vocal fold vibration. The equipment used in the included studies was the Phonatory Aerodynamic System.…”
Section: Evaluation Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…40,41 The softwares used in the included studies were the Computerized Speech Lab, 12,24,29 the Multi-Dimensional Voice Program, [13][14][15]22,24,41 the standardized commercial voice analysis system, 16 the Praat software, 23,26,28,41 and the XION Medical DIVAS 2.5 Digital Voice Analysis. 25 The aerodynamic assessment includes the transglottic flow and the subglottic pressure to understand the variations in pressure and airflow during vocal fold vibration. The equipment used in the included studies was the Phonatory Aerodynamic System.…”
Section: Evaluation Methodsmentioning
confidence: 99%
“…One method was clinical evaluation by a speech-language pathologist [12][13][14][15][16][17][18][19]23 or otolaryngologist. 27,28 The other was a caregiver assessment questionnaire, which comprised the Pediatric Voice Handicap Index, 15,25,27,29 Pediatric Voice Outcome Survey, 26 and visual analog scale. 29…”
Section: Evaluation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Part of the studies suggest that hypertrophic tonsils have hypernasality as a concomitant symptom that decreases postoperatively and thus leads to an improvement of voice quality [10]. However, some studies have shown that after tonsillectomy, only a subjective experience of voice improvement occurs, but this is not confirmed by objective measurements [11,12].…”
Section: Introductionmentioning
confidence: 99%